2013
DOI: 10.1186/1471-2458-13-1149
|View full text |Cite
|
Sign up to set email alerts
|

Experiences on recruitment and retention of volunteers in the first HIV vaccine trial in Dar es Salam, Tanzania - the phase I/II HIVIS 03 trial

Abstract: BackgroundEventual control of HIV/AIDS is believed to be ultimately dependent on a safe, effective and affordable vaccine. Participation of sub-Saharan Africa in the conduct of HIV trials is crucial as this region still experiences high HIV incidences. We describe the experience of recruiting and retaining volunteers in the first HIV vaccine trial (HIVIS03) in Tanzania.MethodsIn this trial enrolled volunteers from amongst Police Officers (POs) in Dar es Salaam were primed with HIV-1 DNA vaccine at months 0, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Lack of social support was mentioned as a reason for non‐participation 23 times , ranked in the top three eleven times , and given as the top reason three times . Lack of social support was found to be ranked higher (third) for research being conducted in Asia, involving HIV and women, whilst playing a smaller role in the regions of Sub‐Saharan Africa, North Africa and the Middle East and Eastern Europe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of social support was mentioned as a reason for non‐participation 23 times , ranked in the top three eleven times , and given as the top reason three times . Lack of social support was found to be ranked higher (third) for research being conducted in Asia, involving HIV and women, whilst playing a smaller role in the regions of Sub‐Saharan Africa, North Africa and the Middle East and Eastern Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Additional reasons given for non‐participation were costs , cultural insensitivity , fear of false‐positive test results after participation in HIV research , fear of knowledge of health status , insufficient compensation , invasive procedures, lack of interest , lack of clarity , not willing to comply to terms of research , no perceived need , feeling overwhelmed , placebo concerns , having had a previous negative experience , not wishing to be re‐contacted , feeling tempted to unsafe behaviour , lack of perceived benefit , effect on lifestyle , worsening medical condition, and having a lack of knowledge about research .…”
Section: Resultsmentioning
confidence: 99%
“…Encouragement from family and friends was shown to be important in successful recruitment and retention of study volunteers [46, 47]. Important motivators for participation included an altruistic desire to contribute to protection from HIV, prevention, eliminating the spread of HIV/AIDS, and improved access to health care services and counseling [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…They found that stepwise education provision and sensitization recruitment enabled them to recruit sufficient number of participants into the clinical trial. However, it took them a year to recruit 60 participants[ 9 ].…”
Section: Introductionmentioning
confidence: 99%